The Art of Wounded Hope: Forced Migration, Prophecy and Aesth/Ethics. Issue 6 (18th August 2018) - Snyder, Susanna
ABSTRACT: This paper constructs an analogy between art and prophecy, exploring and comparing their relationship to political change. It does so through considering arts-based responses to the contemporary forced migration context in conversation with the book of Jeremiah. Recognizing that the artistic – in the case of Jeremiah, the poetic – can be an important means of resistance for those experiencing exile and injustice, this paper delineates two key ways in which visual arts, poetry, music and theater are playing a prophetic role in relation to migration today. First, the arts can generate prophetic revelation, helping people to see more clearly and truthfully the pain and suffering experienced by forced migrants. Second, the arts can enliven prophetic imagination, helping people to visualize creatively how a world-in-migration could be at its best by offering glimpses of oneness and hope. The paper concludes by pointing out some ambiguities involved in engaging with the arts as a means of prophecy.